การวิเคราะห์และนำเสนอแนวทางพัฒนาค่านิยมทางภาษาไทยของนักเรียนมัธยมศึกษาตอนต้น : การิจัยแบบผสม - เยาวลักษณ์ หงษ์หิรัญเรือง (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The present study was a mixed method research which aimed to 1) analyze the levels of Thai language values perceived by lower secondary school students, 2) compare the levels of Thai language values perceived by students in two different school areas, namely public schools in Bangkok and public schools in the greater Central Region, and 3) propose guidelines for lower secondary school teachers in developing Thai language values among their students. The research sample was 955 Mattayomsuksa 2 (Grade 8) students by using multi-stage random sampling. The dependent variable was Thai language values which comprised components namely Awareness of Thai language, Pride in Thai language, and Need to conserve Thai language, and the independent variable was school locations which were specified as Bangkok and central provinces. There were two types of data. Quantitative data were collected using a 5-scale rating which measured a Thai Language Value Test of which reliability, measured by Cronbach’s alpha coefficient, was between 0.76-0.85 analyzed using descriptive statistics, T-test, Pearson correlation, confirmatory factor analysis, and multiple group analysis. Qualitative data were gathered through focus-group interviews and classroom observation and analyzed by content analysis. Research findings can be concluded as follows:1) On average, Thai language values of lower secondary school students were at a moderate level of 3.35. In terms of individual components, it was found that Pride in Thai language received a higher average score than the other two components at 3.41. The average scores for Awareness of Thai language and Need to conserve Thai language were 3.40 and 3.23, respectively. In addition, Pride in Thai language had the greatest factor loading among the three components of Thai language values, followed by Need to conserve Thai language and Awareness of Thai language, respectively.2) The overall Thai language values of lower secondary school students in Bangkok did not differ from those of students in the greater Central Region. However, it was found that there was a statistical significance at .05 in the comparison between these two groups of students in terms of their perceptions of Pride and Need. Furthermore, factor loading of the three components was found dissimilar between the two groups. For students in Bangkok, Need to conserve Thai language received the greatest factor loading, followed by Pride in Thai language and Awareness of Thai language, respectively. For students in other Central provinces, Pride in Thai language received the greatest factor loading, followed by Awareness of Thai language and Need to conserve Thai language, respectively.3) In terms of guidelines for the development of Thai language values among lower secondary school students, the findings suggested that Thai language teachers should attract students’ interest in Thai language through classroom activities and interesting materials. Teachers should place an emphasis on the significance of Thai language by organizing extra-curricular activities and arranging a learning atmosphere to promote awareness of Thai language. Teachers should act as good role models in fostering Thai language use both inside and outside classrooms. Furthermore, teachers should enforce Thai language values through praise or awards. Teachers should encourage peer-tutoring for Thai language use and the sharing of Thai language knowledge. Schools should also issue a policy to promote the conservation of Thai language among teachers and students.